Leadership development through workplace learning in Malaysian organizations - Abdul Wahat, Nor Wahiza; Krauss, Steven Eric; Othman, Jamilah (Canadian Center of Science and Education, 2013)
This paper focuses on leadership development of successful leaders via informal workplace learning in several Malaysian organizations. Leadership development, which involves a life-long process of learning beginning from childhood and one’s early educational experiences, often continues with experiential learning in the workplace. Though many previous studies have explored leadership development via formal programmes in workplaces, there have been limited studies that narrate the contribution of informal learning in workplaces. Hence, we conducted in-depth interviews with five top management team members (TMT) of organizations in the Malaysian higher education, banking and service industries to understand their leadership development experiences. The results included the overarching theme that leadership development should never be separated from organizational priorities, as leaders are the ones who define an organization’s future. The three sub-themes which emerged in relation to leadership development in the context of workplace learning were: (a) the role of informal mentoring in leadership development; (b) observation and reflection during leadership development; and (c) developmental, challenging assignments in leadership development. The findings are presented along with implications for leadership development research and practices in organizations.